The Legal Status of a Foreign Company Branch - Shuhab Hamad, Samir (Journal of Legal Studies and Researches, 2026)
This study examines the legal status of foreign company branches in Iraq, concluding that they are not independent legal entities but extensions of their parent companies, which bear full responsibility for their obligations and activities. The study also compares Iraqi, Egyptian, and French laws and recommends clarifying the legal status of foreign branches, strengthening oversight, and enhancing parent company accountability to better protect third parties.